Notch effect on the liability of welded joints to intergranular fracture - Yuri V. Poletaev; Valery Yu. Poletaev; Dmitri V. Rogozin (Advanced Engineering Research, 2015)
The work objective is to study the surface notch impact on the liability of the heat affected zone (HAZ) of welded joints of the heat-resistant high-alloy steels to brittle intergranular fracture. The theoretical justification is presented, and experiments that demonstrate the mechanism of this effect are described. The impact of the notch acuity of Charpy- and Mesnager-type on the welds life of 12H18N12T, 07H18N9 03H16N9M2 steel at high-temperature (T = 823K) low-frequency low-cycle loading simulating the conditions of a non-stationary operation mode of the equipment and pipelines of the nuclear power plants with fast-neutron reactors is investigated. It is found that the welds of the steels under study exhibit different notch sensitivity depending on the plastic properties and liability to the HAZ metal dispersion hardening. As a result of the work, the significance of the high ductility of the austenite grains free from the second-phase dispersed precipitates reinforcing matrix is shown by experiments. The high resistance of the metal of the HAZ of 03H16N9M2 low-carbon steel from the intergranular fracture is due to this factor. The findings lead to the following conclusion: “minor” surface notches - technological defects such as notch groove, lack of fusion, tear - are unacceptable when operating with welded joints of heat-resistant steels under the high-temperature low-frequency low-cycle loading.